Oxford reading tree: The treasure chest - Roderick Hunt (Karachi; Oxford University Press, 2012)
The Level 6 Biff, Chip and Kipper Stories provide humorous storylines to engage and motivate children. The popular characters and familiar settings are brought to life by Roderick Hunt and Alex Brychta. The stories are unchanged from the previous edition but the cover notes have been updated to support adults in sharing the story with the child.
Keywords: Readers (Elementary)